Revision of the New World genus Glyphidops Enderlein (Diptera: Neriidae) - Sepúlveda, Tatiana A.; Wolff, Marta I.; de Carvalho, Claudio J.b. (Zootaxa, 2014)
The genus Glyphidops Enderlein, 1922, the most widespread and speciose of the New World genera of Neriidae (Diptera), is revised herein. Glyphidops (Glyphidops) ruselatus, new species, G. (G.) steyskali, new species and G. (G.) coracinus, new species are described. Of the 16 previously described species, which were last treated by Aczél (1961), the following synonyms are proposed: Chaetomeristes peruanus Enderlein is treated as a junior synonym of G. (G.) bullatus (Enderlein); Nerius dispar Cresson, Oncopsia neutra Hennig and Oncopsia dubia Hennig are treated as junior synonyms of G.(O.) durus (Cresson) and Oncopsia seductrix Hennig, is treated as a junior synonym of G. (O.) flavifrons (Bigot). The species Telostylus vittatus Cresson, is removed from synonymy with G. (G.) filosus (Fabricius) and revalidated as senior synonym of G. ochreus Hennig. A new diagnosis for the genus and all species are provided, as is an identification key to species. New locality records are provided for Costa Rica, Colombia, Venezuela, Guyana, Ecuador and Brazil.